Physical and mathematical simulation of biological shielding - Batiy, V.G.; Glebkin, S.I.; Yegorov, V.V.; Zakrevskiy, Yu.A.; Kouzmenko, V.A.; Pravdyvyi, A.A.; Fedorchenko, D.V. (Вопросы атомной науки и техники, 2004)
Biological shielding physical simulation and angular distribution measurement method within the “Shelter” object conditions using “Ekran” facility was considered. Method for biological shielding mathematical simulation using data obtained with ShD-1 facility is presented. It is shown that results of mathematical simulation have satisfactory agreement with those obtained with “Ekran” facility.